Positive electrode slurry and preparation method and application thereof
By using hydrogenated nitrile rubber and other conductive agents in the positive electrode slurry of lithium-ion batteries, the energy density and electrical performance of the battery are optimized, the stability problem of the battery at high voltage is solved, and the cycle stability and battery life are achieved.
Patent Information
- Application Number
- CN202411907061.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
When existing lithium-ion batteries increase voltage to increase energy density, the collapse of the positive electrode skeleton and the irreversible surface reaction increase, resulting in a decrease in battery life, and the dispersant will decompose or react with the positive electrode material at high voltage, reducing battery capacity and cycling stability.
Hydrogenated nitrile rubber is used as a dispersant and prepared by emulsion polymerization and hydrogenation reaction. Combining single-walled carbon nanotubes, single-layer graphene and conductive carbon spheres as conductive agents, the positive electrode slurry formula is optimized, the conductivity of the conductive paste is improved and the amount of conductive agent is reduced.
The energy density and compaction density of lithium-ion batteries are improved, the electrical performance and cycle stability of the electrodes are enhanced, and the life of the battery is extended.
Smart Images

Figure CN119725539A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a positive electrode slurry and a preparation method and application thereof. Background Art
[0002] At present, the lithium-ion battery manufacturing industry is facing a particularly prominent challenge in the process of technological innovation: how to better meet the market demand for smaller, thinner and lighter portable electronic products, which is particularly evident in the field of smart phones. To meet this demand, improving the performance of lithium-ion batteries has become a top priority, and the optimization and improvement of the performance of the positive electrode material as the active material of the battery positive electrode is the key factor restricting the improvement of the overall battery performance.
[0003] Increasing the voltage can cause the positive electrode of the battery to release a larger capacity, which is a direct means to increase the energy density of the battery. However, this is accompanied by the collapse of the positive electrode skeleton and the increase of irreversible surface reactions, which leads to a decrease in the life of the lithium-ion battery. This structural instability will limit the use of the battery at high voltage, thus affecting the improvement of the battery energy density. Taking lithium cobalt oxide as an example, when the voltage exceeds 4.35V, the structure of lithium cobalt oxide changes from M1 to H3 phase. At this time, the structure is already in an unstable state, and polyvinyl pyrrolidone (PVP) is currently used as a dispersant in the positive electrode conductive agent. This dispersant will decompose or react with the positive electrode material under high voltage, thereby reducing the battery capacity and cycle stability, and inhibiting the kinetic performance of the lithium battery. Therefore, how to improve the energy density of the battery has become a problem that needs to be solved urgently. Summary of the invention
[0004] The object of the present invention is to provide a positive electrode slurry and a preparation method and application thereof, wherein the positive electrode slurry can improve the energy density of a lithium ion battery.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a positive electrode slurry, which comprises: 0.003-0.01% of dispersant, 0.3-1.0% of conductive agent, 98-98.7% of positive electrode material, and 1-1.3% of binder, based on the mass of dispersant, conductive agent, positive electrode material and binder being 100%;
[0007] The positive electrode slurry further includes a first solvent, and the solid content of the positive electrode slurry is 69.8-72.0 wt %;
[0008] The dispersant is hydrogenated nitrile rubber;
[0009] The preparation method of the hydrogenated nitrile rubber comprises:
[0010] Mix butadiene and acrylonitrile and perform emulsion polymerization to obtain nitrile rubber;
[0011] The nitrile rubber, the second solvent and a platinum catalyst are mixed and subjected to a hydrogenation reaction to obtain hydrogenated nitrile rubber.
[0012] Preferably, the conductive agent includes one or more of conductive carbon balls, single-walled carbon nanotubes and single-layer graphene; the positive electrode material includes one or more of lithium carbonate, lithium manganese oxide, nickel-cobalt-manganese ternary material, lithium cobalt oxide and lithium-rich manganese-based material; the binder includes polyvinylidene fluoride, polyurethane or polyamide imide.
[0013] Preferably, the first solvent comprises N-methylpyrrolidone.
[0014] Preferably, the mass ratio of butadiene to acrylonitrile is 4:1; the temperature of the emulsion polymerization reaction is 80-100° C., and the time is 6-10 hours.
[0015] Preferably, the second solvent includes DMF or THF; and the platinum-based catalyst includes platinum or platinum black.
[0016] Preferably, the mass volume ratio of the nitrile rubber, the second solvent and the platinum catalyst is 10-12 g:100 mL:1-1.5 g.
[0017] Preferably, the temperature of the hydrogenation reaction is 100-120° C. and the time is 6-10 hours.
[0018] The present invention provides a method for preparing the positive electrode slurry, comprising the following steps:
[0019] Mixing the dispersant, the conductive agent, the binder and the first solvent to obtain a conductive paste;
[0020] The conductive slurry is mixed with a positive electrode material to obtain a positive electrode slurry.
[0021] Preferably, the solid content of the conductive paste is 0.7-1.0 wt %.
[0022] The present invention also provides the use of the positive electrode slurry or the positive electrode slurry prepared by the above preparation method in a lithium ion battery.
[0023] Beneficial effects of the present invention:
[0024] The present invention provides a formula for a positive electrode slurry. By changing the types of conductive agent and dispersant in the positive electrode slurry formula, not only the conductivity of the conductive slurry is improved, but also the amount of conductive agent used is reduced, thereby increasing the proportion of positive electrode materials in the positive electrode slurry, thereby increasing the energy density of the lithium-ion battery; and also increasing the compaction density of the electrode sheet, further increasing the energy density. The positive electrode slurry of the present invention improves the electrical properties of the electrode sheet, and obtains a lithium-ion battery with a greater compaction density, better cycle stability, and higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention provides a hydrogenated nitrile rubber preparation reaction process;
[0026] Figure 2 This is a storage comparison chart of the battery cell prepared in Example 1 and the battery cell prepared using PVP as a dispersant at 80°C. DETAILED DESCRIPTION
[0027] The present invention provides a positive electrode slurry, which comprises: 0.003-0.01% of dispersant, 0.3-1.0% of conductive agent, 98-98.7% of positive electrode material, and 1-1.3% of binder, based on the mass of dispersant, conductive agent, positive electrode material and binder being 100%;
[0028] The positive electrode slurry further includes a first solvent, and the solid content of the positive electrode slurry is 69.8-72.0 wt %;
[0029] The dispersant is hydrogenated nitrile rubber;
[0030] The preparation method of the hydrogenated nitrile rubber comprises:
[0031] Mix butadiene and acrylonitrile and perform emulsion polymerization to obtain nitrile rubber;
[0032] The nitrile rubber, the second solvent and a platinum catalyst are mixed and subjected to a hydrogenation reaction to obtain hydrogenated nitrile rubber.
[0033] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.
[0034] In the positive electrode slurry provided by the present invention, the mass fraction of the dispersant is preferably 0.003-0.01%, and more preferably 0.003-0.005%; the dispersant is preferably hydrogenated nitrile rubber. By using hydrogenated nitrile rubber as a dispersant for single-walled carbon nanotubes / single-layer graphene, a stable conductive slurry can be obtained, thereby further improving the energy density of the battery cell.
[0035] The present invention preferably mixes butadiene and acrylonitrile to perform emulsion polymerization to obtain a nitrile rubber; Figure 1As shown, the nitrile rubber is dissolved in a second solvent, a platinum catalyst is added, a nitrogen atmosphere is loaded to discharge the air in the reactor, hydrogenation is performed, a hydrogenation reaction is performed under the action of the platinum catalyst, ethanol is used to condense the rubber, and a highly saturated hydrogenated nitrile rubber (saturation> 99%) is obtained after drying ( Figure 1 In the structural formula, l1≤60, l2=2100~4000, m=150~300, n=700~800, and the overall molecular weight is 200000~300000Da), recorded as HNBR.
[0036] In the present invention, the mass ratio of butadiene to acrylonitrile is preferably 4:1.
[0037] In the present invention, the temperature of the emulsion polymerization reaction is preferably 80 to 100° C., more preferably 80 to 90° C., and the time is preferably 6 to 10 hours, more preferably 6 to 8 hours.
[0038] In the present invention, the second solvent is preferably DMF or THF, and more preferably DMF.
[0039] In the present invention, the platinum-based catalyst is preferably platinum or platinum black, and more preferably platinum black.
[0040] In the present invention, the mass volume ratio of the nitrile rubber, the second solvent and the platinum catalyst is preferably 10-12 g:100 mL:1-1.5 g, and more preferably 10 g:100 mL:1 g.
[0041] In the present invention, the hydrogen concentration in the hydrogenation treatment is preferably 1.0-5.0 MPa, more preferably 1.4-5.0 MPa; the temperature of the hydrogenation reaction is preferably 100-120°C, more preferably 110-120°C, and the time is preferably 6-10 h, more preferably 6-8 h.
[0042] In the positive electrode slurry provided by the present invention, the mass fraction of the conductive agent is preferably 0.3-1.0%, and more preferably 0.35-1.0%; the conductive agent preferably includes one or more of conductive carbon balls, single-walled carbon nanotubes and single-layer graphene, and more preferably single-walled carbon nanotubes and conductive carbon balls; when there are multiple conductive agents, the present invention does not specifically limit the mass ratio between the conductive agents, and the total mass of the conductive agent satisfies a mass ratio of 0.3-1.0%; the present invention selects single-walled carbon nanotubes and single-layer graphene as conductive agents, and the obtained positive electrode sheet has a lower doping amount of the conductive agent under the same conductivity, thereby reducing the amount of the conductive agent used.
[0043] In the positive electrode slurry provided by the present invention, the mass fraction of the positive electrode material is preferably 98-98.7%, and more preferably 98-98.68%; the positive electrode material preferably includes one or more of lithium carbonate, lithium manganese oxide, nickel-cobalt-manganese ternary material, lithium cobalt oxide and lithium-rich manganese-based material, and further preferably includes one or more of lithium carbonate, lithium manganese oxide, nickel-cobalt-manganese ternary material and lithium cobalt oxide, and more preferably includes one or more of lithium carbonate, lithium manganese oxide and nickel-cobalt-manganese ternary material.
[0044] In the positive electrode slurry provided by the present invention, the mass fraction of the binder is preferably 1 to 1.3%, and more preferably 1 to 1.2%; the binder is preferably polyvinylidene fluoride, polyurethane or polyamideimide, and more preferably polyvinylidene fluoride.
[0045] In the present invention, the solid content of the positive electrode slurry is preferably 69.8 to 72.0 wt %, and more preferably 70.0 to 72.0 wt %.
[0046] The present invention provides a method for preparing the positive electrode slurry, comprising the following steps:
[0047] Mixing the dispersant, the conductive agent, the binder and the first solvent to obtain a conductive paste;
[0048] The conductive slurry is mixed with a positive electrode material to obtain a positive electrode slurry.
[0049] The present invention preferably mixes the dispersant with the conductive agent, mixes the obtained mixture with the first solvent, and adds the mixture into a stirring tank to obtain a conductive paste; the solid content of the conductive paste is preferably 0.7-1.0wt%, more preferably 0.8-1.0wt%.
[0050] In the present invention, the positive electrode material is preferably added to the conductive slurry for dispersion to obtain a stable positive electrode slurry; the dispersion time is preferably 3 to 6 hours, and more preferably 3 to 4 hours.
[0051] The present invention also provides the use of the positive electrode slurry or the positive electrode slurry prepared by the above preparation method in a lithium ion battery.
[0052] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0053] Example 1
[0054] The positive electrode slurry provided in this embodiment, based on the mass of the dispersant, the conductive agent, the positive electrode material and the binder being 100%, comprises:
[0055] Hydrogenated nitrile rubber 0.005%, single-walled carbon nanotubes 0.05%, conductive carbon balls 0.3%, lithium cobalt oxide 98.68%, PVDF 1%;
[0056] The positive electrode slurry further includes N-methylpyrrolidone, and the solid content of the positive electrode slurry is 72.0wt%;
[0057] Butadiene and acrylonitrile are mixed in a mass ratio of 4:1, and an emulsion polymerization reaction is carried out at 80°C for 6 hours. After condensation with ethanol, the nitrile rubber is dried to obtain the nitrile rubber.
[0058] 10g of nitrile rubber was dissolved in 100mL of DMF, 1g of platinum black was added, nitrogen atmosphere was loaded to exhaust the air in the reactor, hydrogenation was carried out at 1.4MPa, and hydrogenation reaction was carried out under the action of a catalyst at a reaction temperature of 110°C for 6h to obtain hydrogenated nitrile rubber with a saturation of >99%;
[0059] The hydrogenated nitrile rubber and the single-walled carbon nanotubes were added to N-methylpyrrolidone, and then the conductive carbon balls and PVDF were added, and the mixture was stirred and dispersed for 60 minutes to obtain a conductive slurry with a solid content of 1.0 wt%;
[0060] Lithium cobalt oxide was added to the conductive slurry and dispersed at high speed for 180 minutes to obtain a stable positive electrode slurry.
[0061] Example 2
[0062] The only difference from Example 1 is:
[0063] The positive electrode slurry provided in this embodiment, based on the mass of the dispersant, the conductive agent, the positive electrode material and the binder being 100%, comprises:
[0064] Hydrogenated nitrile rubber 0.003%, single-layer graphene 0.3%, conductive carbon ball 0.3%, lithium iron phosphate 98.32%, PVDF 1%;
[0065] The positive electrode slurry further includes N-methylpyrrolidone, and the solid content of the positive electrode slurry is 69.0wt%;
[0066] The hydrogenated nitrile rubber and the single-layer graphene were added to N-methylpyrrolidone, and then the conductive carbon balls and PVDF were added, and the mixture was stirred and dispersed for 60 minutes to obtain a conductive slurry with a solid content of 1.0 wt%;
[0067] Lithium iron phosphate was added to the conductive slurry and dispersed at high speed for 180 minutes to obtain a stable positive electrode slurry.
[0068] Example 3
[0069] The only difference from Example 1 is:
[0070] The positive electrode slurry provided in this embodiment, based on the mass of the dispersant, the conductive agent, the positive electrode material and the binder being 100%, comprises:
[0071] Hydrogenated nitrile rubber 0.003%, single-layer graphene 0.3%, conductive carbon ball 0.3%, nickel-cobalt-manganese ternary material 98.12%, PVDF 1%;
[0072] The positive electrode slurry further includes N-methylpyrrolidone, and the solid content of the positive electrode slurry is 69.0wt%;
[0073] The hydrogenated nitrile rubber and the single-layer graphene were added to N-methylpyrrolidone, and then the conductive carbon balls and PVDF were added, and the mixture was stirred and dispersed for 60 minutes to obtain a conductive slurry with a solid content of 1.0 wt%;
[0074] The nickel-cobalt-manganese ternary material was added to the conductive slurry and dispersed at high speed for 180 minutes to obtain a stable positive electrode slurry.
[0075] Comparative Example 1
[0076] The only difference from Example 1 is:
[0077] No single-walled carbon nanotubes were added to the cathode slurry;
[0078] The positive electrode slurry of Comparative Example 1 was obtained.
[0079] Comparative Example 2
[0080] The only difference from Example 1 is:
[0081] Replace PVDF with polyvinylpyrrolidone;
[0082] Obtaining the positive electrode slurry of Comparative Example 2;
[0083] Comparative Example 3
[0084] The only difference from Example 2 is that:
[0085] No single-layer graphene was added to the cathode slurry;
[0086] The positive electrode slurry of Comparative Example 3 was obtained.
[0087] Performance measurement
[0088] The positive electrode slurries obtained in Examples 1 to 2, Comparative Example 1 and Comparative Example 3 were respectively coated, rolled, slit, sheeted and wound to obtain a battery cell with a conventional structure.
[0089] 1. The electrode diaphragm resistance was tested using a diaphragm resistance meter, and the compaction density (weight / thickness) and energy density (energy / volume) were calculated using the electrode thickness and the cell thickness. The compaction density, energy density and diaphragm resistance of the cells prepared with the positive electrode slurries of Examples 1 to 2, Comparative Example 1 and Comparative Example 3 are shown in Table 1.
[0090] Table 1 Performance results of battery cells in Examples 1 to 2, Comparative Examples 1 and 3
[0091] Example 1 Example 2 Comparative Example 1 Comparative Example 2 <![CDATA[Compaction density (g / cm 3 )]]> 4.25 2.3 4.10 2.2 Energy density (Wh / L) 730.8 459.7 720 450.4 Diaphragm resistance(Ω) 1.74 0.89 2.28 1.38
[0092] As shown in Table 1, compared with Comparative Example 1 (formulation without adding single-walled carbon nanotubes), the compaction density of the positive electrode sheet obtained by the positive electrode slurry of Example 1 is increased from 4.10 g / cm 3 Increased to 4.25g / cm 3 , the energy density is increased by about 1.5%, and the membrane resistance is reduced from 2.28Ω to 1.74Ω; compared with Comparative Example 3 (formula without adding single-layer graphene), the compaction density of the positive electrode sheet obtained by the positive electrode slurry of Example 2 is reduced from 2.2g / cm 3 Increased to 2.3g / cm 3 , the energy density is increased by 0.7%, and the diaphragm resistance is reduced from 1.38Ω to 0.89Ω, and the 2C rate discharge performance is 1.3% higher.
[0093] 2. Determine the thickness expansion rate of the lithium ion battery cells prepared in Example 1 and Comparative Example 2 at different times at 80°C. The results are shown in Figure 2 .
[0094] like Figure 2 As shown, compared with the battery cell of comparative example 2 (using polyvinyl pyrrolidone as dispersant), under the same ratio, the battery cell of embodiment 1 (using HNBR as dispersant) is stored at 80°C, and the 24H thickness expansion rate is about 5% lower. Compared with the battery cell made in comparative example 2, under the same ratio, the battery cell made in embodiment 1 shows better performance under the extreme storage condition of 80°C. Specifically, after 116 hours of thermal measurement, its thickness expansion rate is about 10%; while the thickness expansion rate of comparative example 2 (i.e., the battery cell using polyvinyl pyrrolidone as dispersant) has exceeded 10% after only 30 hours of thermal measurement. It shows that the lithium-ion battery cell prepared by the positive electrode slurry of embodiment 1 has better structural stability and safety.
[0095] It can be seen from the above embodiments that the present invention provides a positive electrode slurry, which improves the conductivity of the conductive slurry and reduces the amount of conductive agent used by changing the types of conductive agent and dispersant in the positive electrode slurry, thereby not only improving the energy density of the lithium-ion battery, but also improving the electrical performance.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A positive electrode slurry, characterized in that: Taking the mass of dispersant, conductive agent, positive electrode material and binder as 100%, the composition includes: dispersant 0.003-0.01%, conductive agent 0.3-1.0%, positive electrode material 98-98.7%, binder 1-1.3%; The positive electrode slurry further includes a first solvent, and the solid content of the positive electrode slurry is 69.8-72.0 wt %; The dispersant is hydrogenated nitrile rubber; The preparation method of the hydrogenated nitrile rubber comprises: Mix butadiene and acrylonitrile and perform emulsion polymerization to obtain nitrile rubber; The nitrile rubber, the second solvent and a platinum catalyst are mixed and subjected to a hydrogenation reaction to obtain hydrogenated nitrile rubber.
2. The positive electrode slurry according to claim 1, characterized in that The conductive agent includes one or more of conductive carbon balls, single-walled carbon nanotubes and single-layer graphene; the positive electrode material includes one or more of lithium carbonate, lithium manganese oxide, nickel-cobalt-manganese ternary materials, lithium cobalt oxide and lithium-rich manganese-based materials; the binder includes polyvinylidene fluoride, polyurethane or polyamide-imide.
3. The positive electrode slurry according to claim 1, characterized in that The first solvent includes N-methylpyrrolidone.
4. The positive electrode slurry according to claim 1, characterized in that: The mass ratio of butadiene to acrylonitrile is 4:1; the temperature of the emulsion polymerization reaction is 80-100° C., and the time is 6-10 hours.
5. The positive electrode slurry according to claim 1, characterized in that: The second solvent includes DMF or THF; the platinum-based catalyst includes platinum or platinum black.
6. The positive electrode slurry according to claim 1, characterized in that: The mass volume ratio of the nitrile rubber, the second solvent and the platinum catalyst is 10-12 g:100 mL:1-1.5 g.
7. The positive electrode slurry according to claim 1, characterized in that: The temperature of the hydrogenation reaction is 100-120° C. and the time is 6-10 hours.
8. The method for preparing the positive electrode slurry according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mixing the dispersant, the conductive agent, the binder and the first solvent to obtain a conductive paste; The conductive slurry is mixed with a positive electrode material to obtain a positive electrode slurry.
9. The preparation method according to claim 8, characterized in that: The solid content of the conductive paste is 0.7-1.0 wt %.
10. Use of the positive electrode slurry according to any one of claims 1 to 7 or the positive electrode slurry prepared by the preparation method according to any one of claims 8 to 9 in lithium ion batteries.